Comparing Delinquents and Non-Delinquent Siblings with Regard to Social and Personal Resources - Chiam Heng Keng; Chan Siok Gim (Kajian Malaysia, 2004)
Comparison between delinquents and non-delinquent siblings was made using a subsample of 16 male subjects having non-delinquent male siblings close in age. It was part of a bigger study carried out to ascertain whether social and personal resources are related to deviant behaviour of adolescents.